1981
DOI: 10.1136/thx.36.10.752
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of pulmonary artery pressure in chronic obstructive pulmonary disease.

Abstract: In 175 patients with chronic obstructive lung disease (157 chronic bronchitic and 18 emphysematous patients) exhibiting moderate to severe airway obstruction (mean FEV1/vital capacity = 40X2 + 11 1 %), cumulative survival rates calculated by the actuarial method were compared in subgroups according to the initial level of mean pulmonary artery pressure, pulmonary volumes, and arterial blood gases. Patients were catheterised between 1968 and 1972 and were followed for at least five years. The results emphasise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
254
1
18

Year Published

1991
1991
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 421 publications
(285 citation statements)
references
References 14 publications
5
254
1
18
Order By: Relevance
“…Moreover, several reports have suggested that a mean PAP Ͼ29 mm Hg may be associated with significantly shorter survival of patients with COPD. 2,3 It is noteworthy that in our study, such high levels of PAP were observed only in LL patients. Therefore, the presence of the LL genotype should identify patients at risk for developing severe PH during progression of COPD.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Moreover, several reports have suggested that a mean PAP Ͼ29 mm Hg may be associated with significantly shorter survival of patients with COPD. 2,3 It is noteworthy that in our study, such high levels of PAP were observed only in LL patients. Therefore, the presence of the LL genotype should identify patients at risk for developing severe PH during progression of COPD.…”
Section: Discussionmentioning
confidence: 69%
“…1 Although PH is usually mild to moderate in COPD, it is associated with a poor prognosis. 2,3 Long-term oxygen therapy improves the prognosis of patients with COPD and stabilizes pulmonary artery pressure (PAP). 4,5 However, even in patients receiving long-term oxygen therapy, PH is the strongest prognostic factor, independent of the severity of airflow limitation or hypoxemia.…”
mentioning
confidence: 99%
“…T he development of pulmonary hypertension (PH) in chronic lung diseases such as chronic obstructive pulmonary disease (COPD) has both functional and prognostic implications [1,2]. PH in COPD (PH-COPD) is usually mild to moderate with preserved cardiac output, and evolves slowly alongside the progression of lung disease and hypoxaemia [3].…”
mentioning
confidence: 99%
“…2 Hypoxia also plays a significant role in the pathogenesis of the pulmonary hypertension that accompanies chronic obstructive airway disease. 3 Pulmonary hypertension is a serious clinical problem with significant morbidity and mortality, but apart from continuous oxygen administration, there is currently no satisfactory treatment for the condition.…”
mentioning
confidence: 99%